LEGAL PROTECTION OF CONVENTIONAL BANK AS MANDATORY CONVERTIBLE BOND HOLDER - Sutikno, Franciska Mifanyira (Syariah: Jurnal Hukum dan Pemikiran, 2019)
Bank as legal entity has legal right to do Investment to the another party by several investment instrument in Stock Market, Money Market or another agreement. Mandatory Convertible Bond is one of Investment Instrument which has hybird characteristic of Debt and Equity based on the Central Bank Regulatio and International Mandatory Convertible Bond concept leads to the double legal standing to the Bank as the holder. The Objective of this research is to analyze the usage of  Mandatory Convertible Bonds and the protection of Bank as its holder. The result of the research are Mandatory Convertible Bond used as equity participation through debt mechanism and the protection of Bank provided by Prospectus and Trust Agreement.